The Role of Tocotrienol in Arthritis Management-A Scoping Review of Literature - Hashwin Singh Tejpal Singh; Alya Aqilah Aminuddin; Kok-Lun Pang; Sophia Ogechi Ekeuku; Kok-Yong Chin (MDPI AG, 2023)
Arthritis is a cluster of diseases impacting joint health and causing immobility and morbidity in the elderly. Among the various forms of arthritis, osteoarthritis (OA) and rheumatoid arthritis (RA) are the most common. Currently, satisfying disease-modifying agents for arthritis are not available. Given the pro-inflammatory and oxidative stress components in the pathogenesis of arthritis, tocotrienol, a family of vitamin E with both anti-inflammatory and antioxidant properties, could be joint-protective agents. This scoping review aims to provide an overview of the effects of tocotrienol on arthritis derived from the existing scientific literature. A literature search using PubMed, Scopus and Web of Science databases was conducted to identify relevant studies. Only cell culture, animal and clinical studies with primary data that align with the objective of this review were considered. The literature search uncovered eight studies investigating the effects of tocotrienol on OA (n = 4) and RA (n = 4). Most of the studies were preclinical and revealed the positive effects of tocotrienol in preserving joint structure (cartilage and bone) in models of arthritis. In particular, tocotrienol activates the self-repair mechanism of chondrocytes exposed to assaults and attenuates osteoclastogenesis associated with RA. Tocotrienol also demonstrated strong anti-inflammatory effects in RA models. The single clinical trial available in the literature showcases that palm tocotrienol could improve joint function among patients with OA. In conclusion, tocotrienol could be a potential anti-arthritic agent pending more results from clinical studies.